Tembang Batanghari Sembilan and Character Building - Yanti Sariasih; Fathiaty Murthado; Zainal Rafli (research, training and philanthropy institution Natural Aceh, 2021)
This paper begins with a concern over the existence of regional oral literature which is increasingly